2020
DOI: 10.18231/j.ijogr.2020.049
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent process before caesarean section: A study of patient’s perspective regarding adequacy of consent process

Abstract: Informed consent is an ethical and legal requirement and is practiced before all the surgical procedures. Cesarean section is the commonest obstetrics surgery and there is increased rate of C-section due to better diagnosis and early referral. A legitimate consent should be taken from the patient or her guardian before caesarean section. So this study was aimed to assess the adequacy of informed consent process and the understanding of information obtained by the patient. A cross sectional study was done with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was found that the majorities of the patients (81.4% & 91% respectively) were not informed about the type of anesthesia and were not given the chance to choose their anesthetic preference. This finding is comparable with other studies ( 6 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that the majorities of the patients (81.4% & 91% respectively) were not informed about the type of anesthesia and were not given the chance to choose their anesthetic preference. This finding is comparable with other studies ( 6 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the study, only 40.1% agreed to the fact that they were told that they might need surgery in the future during their antenatal visit (P=0.001). This finding is comparable with India's study finding that found 37.5 % of participants were told about the possibility the cesarean section during antenatal visits ( 18 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7,8 Researches on the quality of informed consent concerning obstetric interventions are scanty in developing countries. [9][10][11] This research aims to assess the quality of informed consent in women undergoing CS on both emergency and planned basis and to identify factors associated with quality consent.…”
Section: Introductionmentioning
confidence: 99%